Pelatihan Pengelolaan dan Pemilahan Sampah Pada BUMDes Banjarwaru Sejahtera Untuk Menunjang Kemandirian Masyarakat Desa Banjarwaru - Wanti, Linda Perdana; Ariawan, Radhi; Prasetya, Nur Wachid Adi (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
The Community Service (PKM) activity carried out in Banjarwaru Village aims to empower the community through structured and effective waste management. The partner in this program, namely BUMDes "Banjarwaru Sejahtera," is at the forefront of efforts to realize village economic independence by utilizing waste as one of the economic resources. This activity was initiated with the background of problems faced by the community, especially the low awareness of waste management which results in the accumulation of waste in the surrounding environment which has a negative impact on health and environmental aesthetics. Another problem found is the lack of facilities and infrastructure for waste management. To overcome this, the PKM program that is being run carries various solutions designed according to the needs and potential in Banjarwaru Village. The solutions implemented in this program include education and counseling to increase public awareness of the importance of waste management. This educational activity is carried out through counseling and campaigns that directly involve the village community. The PKM team of Cilacap State Polytechnic also provided additional trash bins at strategic points so that people can easily dispose of trash according to its type. With the implementation of these solutions, the main target to be achieved is to increase public awareness of the importance of waste management and the formation of a more structured waste management system. Through education and provision of facilities, it is hoped that the community can consistently separate waste and actively participate in maintaining the cleanliness of the village environment.